Factorising a Quadratic

  • Google+ icon
  • LinkedIn icon
  • 709 views

Factorising a quadratic polynomial of the form,

ax2 + bx + c = 0

can be done in many depends depending on the values we have for a, b and c. 

Some simple polynomial could be done simply by recognition. For example:

 x2 + 4x + 3 = 0

In this scenario we would use the assumption that the factorisation is of the form:

(dx+e)(fx+g) = 0

and we would consider the values of d, e, f and g.

As the coefficient of the xterm is 1, d and f would both be 1. Hence:

(x+e)(x+g) = 0

Now we need numbers for e and g such that:

e*g = 3 and,

e+g = 4

We find that e = 3 and g = 1 or visa versa. 

Hence we can factorise 

x2 + 4x + 3 = 0 

to (x+3)(x+1) = 0

Hanumanth Srikar K. IB Further Mathematics  tutor, IB Maths tutor, GC...

About the author

is an online GCSE Maths tutor with MyTutor studying at LSE University

Still stuck? Get one-to-one help from a personally interviewed subject specialist.

95% of our customers rate us

Browse tutors

We use cookies to improve your site experience. By continuing to use this website, we'll assume that you're OK with this. Dismiss

mtw:mercury1:status:ok